Differences in Acute Reinforcement Across Reduced Nicotine Content Cigarettes - Perkins, Kenneth A. (Psychopharmacology (Berl), 2020)
RATIONALE: The smallest difference in nicotine that can change a smoker’s cigarette preference is not clearly known. OBJECTIVE: A procedure to efficiently identify the difference in nicotine needed to change cigarette preference could help inform research to gauge effects of a nicotine reduction policy. METHODS: Using a within-subjects design, we assessed preference for research cigarettes varying in nicotine contents (NIC; 18.7, 10.8, 5.3, 2.3, and 1.3 mg/g of tobacco), relative to a very low nicotine cigarette (VLNC; 0.4 mg/g), in 17 adult dependent non-menthol smokers abstinent overnight. Only one NIC was compared vs the VLNC per session, with order of the five NIC contents randomized across sessions on five separate days. Preference for each NIC vs VLNC was determined by validated forced choice procedure, with those NIC chosen more than VLNC indicating greater reinforcement due to greater nicotine per se. Secondarily, less preference for lower NIC (vs VLNC), relative to choice for the highest NIC,18.7 mg/g (vs VLNC), indexed reduced reinforcement. RESULTS: Overall, NIC choices increased as their nicotine increased, as anticipated. Relative to the 0.4 mg/g VLNC, choice was greater for NIC ≥5.3 mg/g but not ≤2.3 mg/g. Correspondingly, relative to choice for the 18.7 mg/g, choice was less for NIC ≤2.3 mg/g but not ≥5.3 mg/g. CONCLUSIONS: Although replication with larger samples and longer access is needed, results indicate nicotine reduction to ≤2.3 mg/g in cigarettes would attenuate reinforcement. This choice procedure may efficiently inform future clinical trials to assess relative reinforcing effects of smoking reduced nicotine cigarettes.